PERILAKU POLA MAKAN PENDERITA DIABETES MELITUS KOTA TERNATE: STUDI KUALITATIF - Wahyuni .; Ramli .; Agustin Rahayu (LEMBAGA PENELITIAN PUBLIKASI DAN PENGABDIAN KEPADA MASYARAKAT UNIVERSITAS MUHAMMADIYAH MALUKU UTARA, 2020)
Healthy lifestyle behavior has now become a trend and the needs of everyone including the people of Ternate city. The application of a healthy lifestyle is done to prevent the increasing prevalence of non- communicable diseases, including diabetes mellitus. The number of people with diabetes mellitus in Ternate city was 19.7% of the total population in Ternate city and the highest percentage in Indonesia in 2011. This study aims to find out how lifestyle behavior, especially in the behavior of diabetics. The analytical method used is descriptive qualitative by conducting in-depth interview to explore the eating habits of diabetics. The application of the informant’s diet is included in the 3J principle that is according to schedule, number and type. Patient’s eating schedule was approximately four times a day: morning, afternoon, evening, and at night. The type of food consumed is local food and is widely available in Ternate, including white rice, brown rice, corn rice, potatoes and taro.